Effect of growth temperature on the physical properties of kesterite Cu2ZnSnS4 (CZTS) thin films - Fatima Zohra Boutebakh; N. Attaf; M. S. Aida (Discover Materials)
Abstract Spray pyrolysis technique was used to deposit Cu2ZnSnS4 (CZTS) thin films onto SLG substrates. The effect of substrate temperature (Tsub), ranging from 300°C to 390°C on their structure and optoelectronic properties. The structural properties reveal that all the prepared CZTS films have a kesterite structure, with a preferential orientation along (112) plane, and presence of secondary phases. XRD data indicated an improvement in crystallinity with an increase in average crystallites size, from 12.29 to 24.73 nm, while Tsub rise up to 390 °C. Raman spectra reveal CZTS formation, with two vibrational modes observed at 335 and 373 cm−1 along with a small Raman peak at 472 cm−1 associated to the Cu2S phase. Transmittance spectra show low values in the visible range with an absorption coefficient of 105 cm−2, The band gap energy (Eg) of the sprayed-CZTS films was consistently found to decrease from 1.6 to 1.38 eV as Tsub is increased from 300 to 390 °C. Hall effect measurements revealed p-type conductivity for all the samples, and the electrical conductivity increased from 1.8 to 150 (Ω.cm)−1 with substrate temperature (Tsub). Overall, experimental results demonstrate that grown CZTS thin films can be considered as a promising absorber material in solar cell devices.